The Prophet's Political Communication and the Islamic Classical Period - Siregar, Muklis; Junaidi, Junaidi; Aminuddin, Aminuddin (Holistic Science, 2024)
The study of political communication in the context of Islamic history, especially during the time of the Prophet and the classical era of Islam, is interesting to listen to because it provides insight into the foundations of Islamic politics and its impact on current political views. This research aims to explore the communication strategies used by the Prophet and early Islamic leaders, as well as interpreting their relevance in the contemporary social and political context of Muslims. Through this research, it is hoped that we can understand the ethical values contained in classical Islamic political communication (650-1258 AD), which can guide today's political leaders and activists. The method used is an analysis of the concepts of the Prophet's thought, the views of leading researchers, and case studies such as the Hudaibiyah Agreement. The results show that the Prophet used various strategies, such as amanah, siddiq, fathanah, and tabliq. The implications of this research are important in facing the current political, social and economic challenges of Muslims, and can make a significant contribution in understanding and applying Islamic political values in building a harmonious and prosperous society.